Simultaneous quantification of pesticides in paddy soil and water using UHPLC-MS/MS and associated dermal health risk assessment - Zaidon, Siti Zulfa (2019)
Pesticides are agrochemicals that, despite having many benefits, pose underlying effects on environment and human. Contamination of pesticides in the environment leads to their exposure to human especially via dermal contact. Farmers are the most susceptible population as they work directly with the pesticides. Regular monitoring is required to observe pesticide residues in the environment. However, low concentration of the pesticide residues in complex matrices hinders the process. The objectives of this study were to study the work practice and the self-reported health symptoms of the farmers, and to simultaneously quantify thirteen commonly used pesticides in paddy soil and water using two optimised and validated methods with ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLCMS/ MS). First, the socio-demographic, work practice and self-reported health symptoms of the farmers were investigated. Then, the extraction method of pesticides in both matrices were optimised based on several previously published methods. The percent of recovery of the methods were compared and further optimised to improve the percent of recovery for all target analytes. Next, the optimised methods were validated by determining recovery, method detection limit (MDL), method quantification limit (MQL), and matrix effect of all analytes. The developed methods were then applied to quantify the target analytes in paddy soil and water samples from Tanjung Karang, Selangor. The concentration of each analyte were employed to assess dermal health risk of paddy farmers. Based on the result, the farmers are predominantly Malay male with average years or working of 27 years. Most of them shower and change clothes after and almost 50% wore PPE during farming activities. Headache and skin rash are two of the most frequently reported health symptoms among the farmers. The optimised UHPLC-MS/MS showed good linearity at calibration points ranging from the IQL to 500 ng mL-1, and the correlation coefficients (R2) for all of the target analytes were higher than 0.999. The developed method for soil samples was optimised and modified based on the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) procedure, followed by a dispersive solid phase extraction (dSPE) clean-up technique. Whereas the developed method for water samples was based on glass fibre and nylon filtration, followed by the solid phase extraction (SPE). The percent of recovery of the target analytes in soil and water were ranged from 74% to 111% and 77% to 117% respectively. The MDL of the target analytes were ranged from 0.03 to 0.4 ng g- 1 in soil, and 0.1 to 10 ng L-1 in water. Meanwhile, MQL in soil and water were ranged from 0.08 to 1 ng g-1 and 0.5 to 25 ng L-1 respectively. The matrix effects were ranged from 67% to 126% and 71% to 136% in soil and water samples respectively. The result of the simultaneous quantification showed that chlorantraniliprole was the highest mean concentration of pesticides in paddy soil (15.82 ng mL-1) and paddy water (6.56 ng mL-1) samples. Fipronil showed the highest dermal hazard quotient (HQ) calculated in paddy soil and water which were 1.10×10-2 and 5.26×10-4 respectively. There was no significant noncarcinogenic dermal health risk due to occupational exposure of target pesticides in paddy soil and water to farmers. Meanwhile, the dermal lifetime cancer risk (LCRdermal) for pymetrozine in paddy soil indicates negligible risk, while LCRdermal of pymetrozine in paddy water indicates potential risk (≥1.0×10-6) to farmers via dermal route. The two improved analytical methods for pesticides analysis in soil and water can be employed in the analysis of pesticide residue environmental and agricultural matrices, consequently contributing in the monitoring pesticide usage in agricultural fields.